Pengaruh Spesialisasi Industri Auditor, Audit Fee, dan Stabilitas Keuangan terhadap Fraudulent Financial Statement dengan Audit Tenure sebagai Variabel Pemoderasi : The Effect of Auditor Industry Specialization, Audit Fee, and Financial Stability on Fraudulent Financial Statements with Audit Tenure as a Moderating Variable - Badriyyah, Salma Ronaa; Pratiwi, Laras; Khodijah, Amalia Siti (Universitas Sumatera Barat, 2025)
This study uses audit tenure as a moderating variable to examine how auditor industry experience, audit fee, and financial stability affect false financial statements. A quantitative approach is used to analyze secondary data from 2021–2024 Indonesia Stock Exchange (IDX) infrastructure sector annual reports. The sample had 36 observations via purposeful sampling. Statistical methods include moderate regression and multiple linear regression. Results reveal that audit fees benefit faked financial statements but auditor industry specialty hurts them. No correlation exists between financial stability and fraudulent financial statements. Audit tenure has not been shown to attenuate the connections between financial stability, audit fee, and auditor industry specialization and false financial statements.